Fall Risk Reduction Program Paired with a Transportation Program in an Underserved, Urban Minority Community: A Qualitative Evaluation - Thelma J. Mielenz; Laura Durbin; Fern Hertzberg; Diana Noble-Hernandez; Julie A. Sorensen (Journal of Aging Research)
This study sought to evaluate A Matter of Balance/Volunteer Lay Leaders (AMOB/VLL) fall prevention curriculum in combination with a “door-through-door” program: Coordinated Older-Adult Senior Transportation Services (COASTS) for older adults living in an urban, underserved community. AMOB/VLL participants were offered eight 2-hour classes as part of the training program. Focus groups were conducted with older adult participants, COASTS mobility facilitators, and AMOB/VLL master trainers. A thematic analysis was conducted, and primary themes relating to curriculum content, cultural relevancy, and outcomes were examined. Older adults and facilitators felt the course was rewarding and led to improvements in mobility and confidence. Master trainers were more critical and recommended simplifying content, with tailored guidance for specific populations. They also recommended increased emphasis on balance and physical activity. Although participants and MoFas felt combining AMOB/VLL and COASTS was rewarding and improved participant mobility, master trainers and participants suggested minor modifications to increase program benefits for urban, underserved communities.